Initial Mapping of the Chicken Blood Plasma Proteome - Corzo, A.; Kidd, M.T.; Pharr, G.T.; Burgess, S.C.; Corzo, A.; Kidd, M.T.; Pharr, G.T.; Burgess, S.C. (International Journal of Poultry Science, 2004)
Proteomics is the study of the entire protein compliment of an organism. The blood plasma is the only tissue in which an organism`s entire proteome may be potentially represented. First results toward mapping the broiler plasma proteome are presented here. Blood was taken from eight 18 day-old representative commercial broiler chickens. Plasma was isolated from each sample and pooled. For initial sample fractioning a 0.4 µl aliquot of the pooled plasma was run on one dimensional sodium dodecyl sulfate polyacrylamide gel electrophoresis. Based on relative amounts of protein, the gel was divided into three fractions. The proteins were in-gel digested with trypsin. Two-dimensional liquid chromatography in-line with electrospray ionization tandem mass spectrometry was then used for "shot-gun" qualitative plasma proteomics. The resulting tandem mass spectra were then searched against the non-redundant chicken protein database. Generally accepted high stringency statistical criteria for protein identification were used. Eighty-four chicken proteins were identified. Our work demonstrates the future potential for plasma proteomics for identifying biomarkers of disease and production in chickens.